Not just phonology: a longitudinal study of dyslexia subtypes based on the distinction between reading accuracy and reading rate - Jabbour-Danial, Maysa; Share, David L.; Shalhoub-Awwad, Yasmin (Frontiers in Language Sciences, 2024)
Previous cross-sectional investigations by Shany and colleagues have provided evidence of double dissociation among dyslexics between word reading accuracy and (pure) word reading rate. A ratedisabled subtype (with intact reading accuracy) evinced deficits only in rapid naming (RAN); An accuracy-disabled subtype (with intact reading rate) showed deficits in phonological awareness (PA) and morphological awareness (MA) but not RAN. The present longitudinal study followed 639 Palestinian Arabic-speaking children from preschool to Grade 1 with the aim of determining (1) whether a dissociation between PA+MA and RAN is apparent among pre-literate preschoolers, (2) whether the PA+MA-disabled subgroup constitutes a mild form of Developmental Language Disorder (DLD), (3) whether our three disabled subgroups (PA+MA-only, RAN-only, and PA+MA-plus-RAN) can be differentiated on preschool early literacy measures and, (4) whether the three at-risk subgroups develop into selectively rate-disabled, accuracy-disabled, or doubly-disabled (accuracy+rate) readers in Grade 1?Our findings confirmed the existence of two distinct selectively disabled/at-risk subgroups in preschool: a RAN-only subgroup with intact PA and MA and a PA+MA subgroup with broad impairments across language measures but intact RAN. Grade 1 reading data also confirmed that the RAN-disabled subgroup became slow but accurate readers, whereas the PA+MA subgroup developed into inaccurate and slow readers. Our study indicates partial dissociation between early dyslexia subtypes, each displaying distinct and non-overlapping cognitive-linguistic profiles in preschool. The study also revealed a strong association between reading accuracy and reading rate among beginning readers. This study emphasizes the importance of considering heterogeneity in reading outcomes as well as multiple oral language skills beyond the well-documented role of PA.